(untitled) (Stavební obzor - Civil Engineering Journal, 2021)
This article relies on the reinforcement project of the Mulinghe cable-stayed bridge to explore the changes in the mechanical properties of the reinforced concrete cable-stayed bridge before and after reinforcement. The bridge has large cable spacing, large internal force of a single cable, and the main beam is mainly Reinforced Concrete. Therefore, structural calculation, disease analysis, and damage state simulation are carried out. Afterwards, the bridge’s commonly used reinforcement methods were compared, and suitable reinforcement schemes were selected. After the reinforcement, the field test was carried out on the cable-stayed bridge, the main beam deflection, the strain of the main beam and the main tower, and the increase in the cable force of the cable- stayed were analyzed. The results show that external prestressed reinforcement is the best way, which can significantly reduce the vertical displacement of the main beam and the horizontal displacement of the main tower, and also improve the stress on the upper and lower edges of the main beam. After the external prestressed reinforcement, the ratio of the observed value to the observed value in the filed load test of the cable-stayed bridge’s decreased significantly. It is up to 31% increase in bending capacity of main beams and up to 24% increase in stiffness. This article is instructive for the reinforcement of the early-built sparse-cable reinforced concrete cable-stayed bridge, while also expanding the scope of implementation of external prestressed reinforcement technology.